2012
DOI: 10.1590/s0102-695x2012005000108
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of hydroethanolic extracts from five species of the Passiflora genus

Abstract: Abstract:The diversifi ed genus Passifl ora is well distributed all over Brazil, and many species have been long used as medicinal plants, mainly against anxiety disturbances. This effect has been attributed to its rich fl avonoid composition. Flavonoids' main class, fl avonoid glycosides, has presented central action, particularly as sedativehypnotic, anxiolytic and analgesic. The objective of the present study was to make a phytochemical screening of fi ve little studied Passifl ora species, in order to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 40 publications
1
30
1
3
Order By: Relevance
“…Up to the present moment, the chemical compounds described in this species are the cyanogenic glycoside passicoccin (Spencer, Seigler, 1985), procyanidin derivatives, flavones-C-glycosides, flavones-8,7-di-O,Cglycosides and flavone-O-diglucoside (Sakalem, Negri, Tabach, 2012). In the present work, vitexin, isovitexin and 2"-O-β-D-glucopyranosyl-vitexin were detected in both types of P. coccinea extracts.…”
Section: Chemical Analyses Of the Extractssupporting
confidence: 49%
“…Up to the present moment, the chemical compounds described in this species are the cyanogenic glycoside passicoccin (Spencer, Seigler, 1985), procyanidin derivatives, flavones-C-glycosides, flavones-8,7-di-O,Cglycosides and flavone-O-diglucoside (Sakalem, Negri, Tabach, 2012). In the present work, vitexin, isovitexin and 2"-O-β-D-glucopyranosyl-vitexin were detected in both types of P. coccinea extracts.…”
Section: Chemical Analyses Of the Extractssupporting
confidence: 49%
“…This results in electrolyte imbalance with K depletion. Some of the methods to determine cyanogenic glycosides are gas-liquid chromatography, 107 ultra-high-performance liquid chromatography 108 coupled with a mass spectrometer, a reversed-phase high-performance liquid chromatography 109 and HPLC. 110…”
Section: Anti Nutritional Factors In Green Leafy Vegetablesmentioning
confidence: 99%
“…an extract of P. incarnata and literature data, compounds 2 and 3 could be identified as schaftoside (2) and isoschaftoside (3), which were also isolated from other Desmodium species, such as D. styracifolium and D. unicatum. [12][13][14]18,[20][21][22][23] Compound 5 also showed the same deprotonated and protonated molecular ions as compound 6 at m/z 563 [MÀH] À /565 [M+H] + ; MS 2 and MS 3 analysis resulted in the same product ions. These findings suggested that compound 5 was a 2-O-pentosyl-x-C-hexosyl-apigenin isomer of compound 6, possibly 2″-O-xylosyl-isovitexin (5) as described by Zielinska et al [5] Compound 1 showed deprotonated and protonated molecular ions at m/z 593 [MÀH] À and 595 [M+H] + .…”
Section: Resultsmentioning
confidence: 78%